2013
DOI: 10.1097/olq.0b013e31827bd66b
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decrease in the Incidence of Genital Warts in Young Danish Women After Implementation of a National Human Papillomavirus Vaccination Program

Abstract: The incidence of GWs decreased substantially among women with high HPV vaccine coverage, pointing to the effect of the national HPV vaccination program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 22 publications
5
89
0
3
Order By: Relevance
“…In Australia, the qHPV vaccination program has led to a significant reduction in HPV prevalence and genital warts, as well as high-grade cervical lesions in young women (9)(10)(11)(12)(13). Marked reductions in HPV prevalence and/or genital warts have also been observed in the United States, Sweden, and Denmark (8,(14)(15)(16)(17). Six years after licensure of the qHPV vaccine in Denmark, a reduced risk of cervical lesions has also been observed at the population level (18).…”
Section: Introductionmentioning
confidence: 87%
“…In Australia, the qHPV vaccination program has led to a significant reduction in HPV prevalence and genital warts, as well as high-grade cervical lesions in young women (9)(10)(11)(12)(13). Marked reductions in HPV prevalence and/or genital warts have also been observed in the United States, Sweden, and Denmark (8,(14)(15)(16)(17). Six years after licensure of the qHPV vaccine in Denmark, a reduced risk of cervical lesions has also been observed at the population level (18).…”
Section: Introductionmentioning
confidence: 87%
“…12 The quadrivalent HPV (6/11/16/18) virus-like particle (qHPV) vaccine is highly efficacious in preventing infection and cervical, vaginal, vulvar, and anal dysplasia caused by HPV 6/11/16/18 as well as HPV 6/11-related condyloma, [13][14][15][16] and the bivalent HPV (16/18) vaccine is highly efficacious against HPV 16/18-related infection and cervical dysplasia. 17 Postlicensure studies have shown a rapid decrease in the incidence of high-grade cervical abnormalities, [18][19][20][21] prevalence of vaccine HPV types, [22][23][24][25][26] and incidence of genital warts [27][28][29][30][31] in vaccinees. Data have shown that prophylactic HPV vaccination is generally safe and well tolerated.…”
Section: What This Study Addsmentioning
confidence: 99%
“…24 Our observed safety findings are also similar to that of other studies, whereby vaccine recipients have higher rates of injection site pain, erythema and swelling, but similar rates of systemic AEs. 32 Given the high vaccine efficacy seen in the clinical trials, and the fact that in the 8 y since its original licensure, the qHPV vaccine has been shown to be highly effective at the population level, with marked reductions in the prevalence of HPV vaccine-type related infection and disease in many countries, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] our findings suggest the vaccine should be equally effective in sub-Saharan African women.…”
mentioning
confidence: 99%